The identity of Rhinella mirandaribeiroi (Gallardo, 1965) (Anura: Bufonidae) and its diagnosis in relation to Rhinella granulosa (Spix, 1824) - Moreno, Julian Sebastián Ramirez; Giaretta, Ariovaldo Antonio (Zootaxa, 2025)
The Rhinella granulosa group is composed of 13 species widely distributed in South America and Panama. The richness of the group may be poorly characterized due to limited characterizations caused by a lack of topotype data. This is the case for Rhinella mirandaribeiroi, which lacks topotypical (from Marajó Island, Pará state, Brazil) characterization in terms of acoustics and molecular data, as well as interpopulation variation, considering specimens from the Cerrado, including its junior synonym Bufo granulosus lutzi (Pirapora, Minas Gerais state, Brazil). At the same time, morphological and acoustic differences seem scarce and subtle compared to R. granulosa, a sister species with contiguous distribution areas. Therefore, an integrative taxonomic approach arises as necessary to assess the status of these species and differentiate them. Here, we present morphological data from recently collected topotypes of R. mirandaribeiroi, as well as acoustic and genetic data from this population. We found acoustic, molecular, and morphological evidence that B. g. lutzi and individuals distributed in the Cerrado belong to the same species of R. mirandaribeiroi, maintaining its condition of synonym. We also found that R. granulosa and R. mirandaribeiroi exhibit a conserved phenotype (morphology and acoustics) and that the presence/absence of a clear vertebral line is not a diagnostic character for both named species. However, R. granulosa and R. mirandaribeiroi show a significant genetic distance and therefore should be maintained as valid species until a better understanding of the distribution of both species is achieved.